Preoperative Single-Fraction Partial Breast Radiotherapy – A Novel Phase I Dose-Escalation Protocol with Radiation Response Biomarkers - Horton, Janet K. (Int J Radiat Oncol Biol Phys, 2015)
This phase I dose-escalation trial evaluates the feasibility of single-dose preoperative partial breast irradiation delivered with external beam techniques in early stage breast cancer patients. No acute dose-limiting toxicity was observed at 15, 18, or 21Gy. Paired pre- and post-radiation imaging and tumor biopsies offer unique insight into the biology of breast cancer radiation response. PURPOSE: Women with biologically favorable early stage breast cancer are increasingly treated with accelerated partial breast radiation (PBI). However, treatment-related morbidities have been linked to the large post-operative treatment volumes required for external beam PBI. Relative to external beam delivery, alternative PBI techniques require equipment that is not universally available. To address these issues, we designed a phase I trial utilizing widely available technology to 1) evaluate the safety of a single radiation treatment delivered preoperatively to the small-volume, intact breast tumor and 2) identify imaging and genomic markers of radiation response. METHODS: Women 55 or older with clinically node negative, ER+ and/or PR+, HER2-, T1 invasive carcinomas or low-intermediate grade in situ disease ≤2cm were enrolled (n=32). Intensity-modulated radiotherapy was used to deliver 15 Gy (n=8), 18 Gy (n=8), or 21Gy (n=16) to the tumor with a 1.5cm margin. Lumpectomy was performed within 10 days. Paired pre- and post-radiation MRI images and patient tumor samples were analyzed. RESULTS: No dose-limiting toxicity was observed. At a median follow-up of 23 months, there have been no recurrences. Physician-rated cosmetic outcomes were good/excellent and chronic toxicities were grade 1-2 (fibrosis, hyperpigmentation) in patients receiving preoperative radiation only. Evidence of dose-dependent changes in vascular permeability, cell density, and expression of genes regulating immunity and cell death were seen in response to radiation. CONCLUSIONS: Preoperative single-dose radiotherapy to intact breast tumors is well-tolerated. Radiation response is marked by early indicators of cell death in this biologically favorable patient cohort. This study represents a first-step towards a novel PBI approach. Preoperative radiation should be tested in future clinical trials as it has the potential to challenge the current treatment paradigm and provide a path forward to identify radiation response biomarkers.